Matrimonial property disputes: Rules and effects - Ahmed, Ahmed Ramadan Mohamed; Zaghloul, Saad Gomaa Gomaa; Bakar, Marina Abu (Linguistics and Culture Review, 2021)
Matrimonial property plays an important role in achieving family stability and in building the society. Therefore, due attention must be given to the reality of the matrimonial property, how it is managed and the rules governing it when disputes about it arise to protect the financial rights of both spouses from any damage that can threaten the stability and development of the society. This study has a number of objectives that can bring about balance regarding the issue of matrimonial property, including: Reaching an accurate definition of matrimonial property, Laying down the rules and guidelines of matrimonial property, Clarifying the legal characterization of matrimonial property.